Professores que ensinam matemática em anos iniciais do ensino fundamental : coerência entre concepções e prática pedagógica - Miotto, Jonatan (2023)
This dissertation presents a discussion on the conception, planning, and pedagogical practice of teachers who teach Mathematics in the early stages of elementary education. It is known that Mathematics is of great importance in education, and it is necessary for students to learn it effectively in order to promote their autonomy. Based on this assumption, the question arises: Is there coherence between the conceptions and pedagogical practice of teachers who teach Mathematics in the early years of Elementary Education? In view of this, considering the reality in which the teacher is inserted, it is necessary to analyze how the teacher relates to the subject and how they systematize this process before actually implementing it in the classroom. Therefore, in order to answer the raised question, the general objective of this study is to analyze the relationships between the conceptions and pedagogical practice of teachers who teach Mathematics in the early years of elementary education. For this purpose, a research was conducted in a school unit in the municipality of Tangará da Serra/MT, which offers classes in the first stage of elementary education. The participants were teachers with different characteristics, such as education, professional experience, and length of service in the early years of basic education, who work with children in the early years at the mentioned educational institution. The research method adopted was qualitative investigation with an interpretive approach. The main result revealed relevant inconsistencies between the conceptions and pedagogical practice of teachers who teach Mathematics in the early years of elementary education. This can be observed in various instances during the observation of these teachers' classes, such as the adopted methodology, the alignment between the planning and what was worked on in the classroom, the resources used, the lack of interaction between students/students, students/teacher, and the oftencontextually disconnected activities, influenced by the traditional teaching model.